2018
DOI: 10.1002/cctc.201800327
|View full text |Cite
|
Sign up to set email alerts
|

How do Core–Shell Structure Features Impact on the Activity/Stability of the Co‐based Catalyst in Dry Reforming of Methane?

Abstract: Dry reforming of methane has been systematically investigated over a series of x‐Co@SiO2‐y catalysts where x is the Co particle size ranging from 11.1 to 121.3 nm while y denotes the silica shell thickness ranging from 6.0 to 21.9 nm. Various techniques including TEM, XRD, H2‐TPR/‐TPD, XPS, BET, O2‐TPO, TG, and H2‐TPSR‐MS were employed to characterize physicochemical properties of catalysts. H2‐TPR and XPS results indicate that the core–shell interaction is dependent on the core size: the smaller the Co partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 80 publications
(72 reference statements)
1
14
0
Order By: Relevance
“…For Co@SiO 2 catalysts Pang et al [17] examined the influence of the shell structure on the activity and selectivity in the dry reforming of methane. However, the composition at the reaction locus is depending on the diffusive transport of reactants and products through the porous shell for material B. Consequently, the diffusion rates governed by the molecular diffusion coefficients and the pore size, as well as the effective diffusion length given by the spatial arrangement of the active nanoparticles inside the supporting shell is important.…”
Section: Co 2 Methanationmentioning
confidence: 99%
See 2 more Smart Citations
“…For Co@SiO 2 catalysts Pang et al [17] examined the influence of the shell structure on the activity and selectivity in the dry reforming of methane. However, the composition at the reaction locus is depending on the diffusive transport of reactants and products through the porous shell for material B. Consequently, the diffusion rates governed by the molecular diffusion coefficients and the pore size, as well as the effective diffusion length given by the spatial arrangement of the active nanoparticles inside the supporting shell is important.…”
Section: Co 2 Methanationmentioning
confidence: 99%
“…Consequently, the loss in active surface area by migration and subsequent coalescence of single atoms or aggregates as well as Ostwald ripening is hardly avoidable, leading to deactivation under reactions conditions. Pang et al [17] examined Co@SiO 2 catalysts in the dry reforming of methane and found that the core size as well as shell thickness need to be carefully balanced in order to ensure a high activity as well as to avoid coking and oxidation of Co cores. These systems offer an improved sinter resistance and allow to tailor the combination of physical and chemical functionalities on the nanoscale, as well as to generate a confinement effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…XRD characterization : The composition, structure, and crystallinity of catalysts after reduction treatment were further analyzed using XRD. Observed in Figure , the diffraction peaks of reduced Co‐30 matched with the standard bulk data of Co, Al 2 O 3 , and CoAl 2 O 4 , confirming the TEM result in Figure (d2) . Meanwhile, for Co‐10, Co‐15, and Co‐20, the diffraction peaks indicate the presence of Co and CoAl 2 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, it has been revealed that the supported Co catalysts show good activity for dry reforming process. [9,[12][13][14][15] Even though the catalytic activity is neither superior to Ni nor to other noble metal catalysts such as Ru and Rh, studies on the supported Co catalysts have reported to produce good catalytic performance with significantly lower carbon deposition. [16,17] Previous study suggested that the rate of carbon deposition and the type of deposited carbon on Co metal are different from that on Ni metal.…”
Section: Introductionmentioning
confidence: 99%